A Study on the Measurement and Influencing Factors of Innovation Governance Performance of Hubei Province in China Based on Technology Heterogeneity - Zelei Xiao; Ye Wang; Lin Yu; Qi Xiong; Hua Jiang (Discrete Dynamics in Nature and Society)
Exploring areas of innovation and development and promoting total factor productivity is a topic that is crucial to implementing innovation-driven strategies and building a modern economic system in the Hubei province in China. So, the aim of the research is to find a methodology for computing innovation performance and its influence factors in the Hubei region of China. Based on the existing efficiency measurement methods, this study measures the innovation efficiency performance and subsequently the innovation performance by using the optimized Färe-Primont index for a sample of 28 manufacturing industries in Hubei. A threshold regression model of multidimensional explanatory variables focusing on business performance, government support, industry openness, and synergic innovation is used to investigate the core factors that affect the improvement of innovation performance in Hubei’s manufacturing industries. Results show that there is a significant “technological heterogeneity” in Hubei’s manufacturing industries. Business performance plays a significant role in promoting the innovation performance of manufacturing industries, while the roles of industry development, government support, and synergic innovation on innovation performance change depending on the “technological characteristics” of industries.